Creating a Picture Card Game For German Vocabulary on The Topic of Quite Mobile - Sheren Triana Sianipar; Tanti Kurnia Sari (PT PUSTAKA CENDEKIA GROUP, 2026)
This study aimed to develop a picture card game for German vocabulary level A2 on the topic of